STUDIES ON BEMISIA TABACI AND ITS MANAGEMENT - Malik, Kamlesh; Singh, B P (Potato Journal, 2013)
Studies employing RAPD-PCR analysis and biological indicator zucchini cultivar Ambassador showed that Bemisia tabaci occurring in western Uttar Pradesh does not belong to B-biotype. Population of B. tabaci in early planted crop peaked by third week of October and started declining thereafter. Best control of B. tabaci and potato apical leaf curl disease was achieved when seed treatment with imidacloprid was followed by aerial spray at emergence and 15 days thereafter. Despite the presence of vector, potato apical leaf curl disease was absent in variety Kufri Bahar while it was serious in other varieties namely Kufri Anand, Kufri Badshah, Kufri Chipsona-I, Kufri Chipsona-2, Kufri Pukhraj and Kufri Sutlej in the unprotected early planted crop.